2022
DOI: 10.1111/jvp.13083
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic modeling of ketoprofen and flunixin at piglet castration and tail‐docking

Abstract: This study performed population‐pharmacokinetic/pharmacodynamic (pop‐PK/PD) modeling of ketoprofen and flunixin in piglets undergoing routine castration and tail‐docking, utilizing previously published data. Six‐day‐old male piglets (8/group) received either ketoprofen (3.0 mg/kg) or flunixin (2.2 mg/kg) intramuscularly. Two hours post‐dose, piglets were castrated and tail docked. Inhibitory indirect response models were developed utilizing plasma cortisol or interstitial fluid prostaglandin E2 (PGE2) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The toxicity of meloxicam in humans and different mammalian species has been well-studied in laboratory animals, companion animals, cattle, and pigs [ 79 , 80 , 81 , 82 ], and meloxicam has consistently been shown to be safe for piglets and adult pigs [ 79 , 80 , 81 ]. It has also been shown to be less toxic than other NSAIDs, as it is a specific COX-2 antagonist [ 82 , 83 , 84 , 85 ]. This study confirmed the safety of topical 4% lidocaine and 0.3% meloxicam, as there were no safety issues, even in piglets receiving three times the nominal dose daily for three subsequent daily treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of meloxicam in humans and different mammalian species has been well-studied in laboratory animals, companion animals, cattle, and pigs [ 79 , 80 , 81 , 82 ], and meloxicam has consistently been shown to be safe for piglets and adult pigs [ 79 , 80 , 81 ]. It has also been shown to be less toxic than other NSAIDs, as it is a specific COX-2 antagonist [ 82 , 83 , 84 , 85 ]. This study confirmed the safety of topical 4% lidocaine and 0.3% meloxicam, as there were no safety issues, even in piglets receiving three times the nominal dose daily for three subsequent daily treatments.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have investigated the efficacy of these drugs in pigs housed under different conditions and treatment regimens [ 18 ]. Most of these studies have focused on their efficacy in relieving pain in piglet castration and their anti-inflammatory potential in experimental models of inflammation [ 18 , 19 , 20 ]. The use of NSAIDs and their effects on the development of gastric lesions in fattening pigs have been little studied.…”
Section: Introductionmentioning
confidence: 99%